Dampak Kecanduan Game Online pada Siswa SMP - Fahrul, Aditya; Nurfarhanah, Nurfarhanah (Lembaga Yasin AlSys, 2025)
Online game addiction among teenagers, especially middle school students, has become an increasingly pressing problem, considering its negative impact on various aspects of students' lives. According to Yunita (2019), the impact of online game addiction has an impact on time, financial, academic, psychological, social and health aspects. This research aims to identify the impact of online game addiction on junior high school students in terms of time. 2. financial aspect. 3. academic aspect. 4. psychological aspect. 5. social aspect. 6. health aspect. The method used in this research is quantitative with descriptive research type. The research sample was 94 students selected using purposive sampling technique. Data was obtained by distributing research instruments in the form of questionnaires on the impact of online game addiction on junior high school students which had been tested for validity and reliability. Data is processed using percentage techniques. The research results show that the impact of online game addiction on students is seen from: 1. In terms of time: forgetting time when playing online games (25.53%). 2. Financial aspect: spending pocket money to buy items in online games (15.95%). 3. Academic aspect: academic grades decrease due to spending more time playing online games (30.85%). 4. Psychological aspect: it is difficult to control emotions when experiencing defeat in an online game (44.68%). 5. Social aspect: it is more comfortable interacting with friends in online games than meeting in person (24.46%) 6. Health aspect: feeling pain in the neck and back due to sitting for too long in front of the screen playing online games (40.42%). The implications of guidance and counseling services that can be provided are individual counseling services, group guidance services and group counseling services.